Implementasi Sistem Akuntabilitas Kinerja Satuan Kerja Perangkat Daerah - Ruscitasari, Zulfatun (Universitas PGRI Yogyakarta, 2019)
This research is motivated by the demand to improve accountability of government performance. The purpose of this study is to evaluate the suitability of information from planning documents to reporting document, as well as to identify factors that contribute in the implementation of a performance measurement system. The analytical tools used in this study include a blueprint performance model used to analyze the accuracy of indicators that have been prepared and thematic analysis for interview results data.Â This research uses a qualitative method. The results of the research show that the performance measurement system from planning to performance achievements at the PUP-ESDM office, Yogyakarta Special Region has not fully demonstrated the suitability of information. In addition, the performance indicators of the official of PUP-ESDM DIY in 2016 they were still oriented for service providers. Factors that caused problems in performance accountability of PUP-ESDM office were: quality of personnel, regulations, leadership commitments, data availability and information systems, rewards and punishment.